Comparison of temperature sensitive electrical parameter based methods for junction temperature determination during accelerated aging of power electronics. (September 2018) - Wuest, F.; Trampert, S.; Janzen, S.; Straube, S.; Schneider-Ramelow, M.
Abstract: This paper compares the most common used temperature sensitive electrical parameters towards their aging dependencies as well as to one another. Therefore a mission profile is extracted from an off shore wind park and a test plan is generated. Insulated Gate Bipolar Transistor (IGBT) power modules are tested against that test plan using active power cycling. The selected temperature sensitive electrical parameters (TSEP) are monitored online during the test and correlated to each other. This way the aging dependence can be extracted, so that the most aging independent TSEP can be used for condition monitoring during wind park operation. Highlights: Turn-off duration measurements can be used to monitor degradation in IGBT modules. Turn-off duration has lower sensitivity to degradation than saturation voltage. Simplified interpretation of IR image data is sufficient for lifetime estimation.